Jogos no ensino de Biologia: uma análise dos trabalhos científicos no ENEBIO e no ENPEC (1997 a 2019) - Mata, Viviane Ribeiro da (2021)
This work is a qualitative approach research, characterized as to data collection procedures as a state-of-the-art bibliographic research on the use of games in Biology Teaching in two traditional scientific events in Science/Biology teaching. The literature review is based on the studies of Gilles Brougére and Roger Caillois. As to its nature, it is a basic-theoretical research because it enables the establishment of new knowledge that can be used in other research. The study aims to know, describe and present the scenario of research, dedicated to the study of the use of games in Biology Teaching, published in two meetings of the area being these the National Meeting of Biology Teaching (ENEBIO) from 2005 to 2018 and the National Meeting of Research in Science Teaching (ENPEC) from 1997 to 2019. The present work sought to answer the following question: What are the characteristics and directions present in the publications of the 2005 to 2018 editions of ENEBIO and 1997 to 2019 editions of ENPEC that used games to teach Biology contents? It was established as an object of study the games in Biology Teaching, being selected papers that presented activities involving games related to Biology contents. After collecting and processing the data, it was possible to verify that the number of studies on the teaching of biology and games is still small. From the analysis it was possible to conclude that there is a movement towards valuing and encouraging the use of games in the teaching of biology, but these are still discrete in terms of the number of published works. It was also possible to verify a positive position by the researchers in relation to the adoption of games as a way to favor the learning of Biology content. Due to the low number of publications found in the researched papers in the seven editions of ENEBIO (2005 - 2018) and in the twelve editions of ENPEC (1997- 2019), there is a need for the development of further research in the area in order to bring more reflections, considerations and contributions regarding the use of games with the aim of favoring the teaching and learning of Biology content, as well as to collaborate with the growth of the area. Within the time frame established for this research, it was noticed that both in the papers published in ENEBIO and those present in ENPEC, the Teaching of Biology and games are presented as an unstable area in terms of growth. It is perceived, therefore, the importance and the need for a greater organization of the area in order to encourage more research to achieve its stability and growth.